Successful Treatment of Stent Knot in the Proximal Ureter Using Ureteroscopy and Holmium Laser. (10th May 2011) - Richards, Masters M.; Khalil, Daniel; Mahdy, Ayman
Abstract : Knotted ureteral stent is rare yet tedious complication that might represent a treatment challenge to the endourologist. Only twelve cases of knotted stent have been reported. Different management options have been reported, including simple traction, ureteroscopy, percutaneous removal, and open surgery. In this paper, we present the successful untying of the knot using ureteroscopy with holmium laser.